Pelatihan Manajemen Keuangan dan Perencanaan Anggaran di Fasilitas Pelayanan Kesehatan - Rita Zulbetti; Resanti Lestari; Perwita (FEB-UP Press, 2022)
Abstract This Community Service activity aims to improve the skills of participants who work or will work in health care facilities in preparing financial reports, determining unit costs, rates and financial plans in order to produce complete, accurate and timely financial reports according to applicable standards. This activity is divided into two phase, namely the survey and the training. The survey phase was carried out a month before the training activity to find out (1) what part they were placed in a health care facility, (2) the obstacles they faced at work and (3) what training was needed to support the job. The results of this activity are (1) At the survey stage it is known that there are obstacles in the work due to lack of knowledge about the health budget, not understanding how to calculate unit costs, ineffective communication with fellow employees. Therefore, it is deemed necessary to take part in the Financial Management and Budget Planning Training at the Health Care Facilities. (2) After the training the participants were very satisfied (60.6%) and 36.8% satisfied with the fiber not giving an opinion of 2.6%. Thus, after participating in the training, participants have the skills to make financial reports and budget planning that are standard, accurate and timely.